Biochemical Characterization of Antiviral Protein from Silk Worm Fecal Matter Bombyx mori (L) - S.B. Hinchigeri2, S. E. Neelagund1 (Recent Research in Science and Technology, 2011)
Introduction: Silkworm fecal matter is considered as one of the important medicinal sources for many infectious diseases. Therefore, we have explored the antiviral protein (AVP) by exploiting the silkworm fecal matter. Present investigation display the biochemical characterization of a novel anti nuclear polyhedrosis virus (NPV) protein from silkworm fecal matter. Material and Methods: Purified AVP was found to be associated with Tetrapyrrole pigments. The associated Tetrapyrrole was separated and analyzed using TLC (Thin layer chromatography) Spectrophotometry and Spectrofluorometry. The antiviral activity determination in both separated components of AVP was done separately. Results: The AVP associated Tetrapyrrole analyzed was found to be monovinyle pheophytine a; the derivative of chlorophyllide a, in which Mg was absent. The antiviral activity was observed only in protein associated with tetrapyrole. Conclusion: The antiviral protein associated tetrapyrole part was found to be monovinyle pheophytine a, is essential for its antiviral activity.